2014
DOI: 10.1590/s1413-78522014000100002
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of stress induced by screws in the vertebral fixation system

Abstract: Objective: To compare, using photoelasticity, internal stress produced by USS II type screw with 5.2 and 6.2 mm external diameters, when submitted to three different pullout strengths. Methods: Two photoelastic models were especially made. The simulation was performed using loads of 1.8, 2.4 e 3.3 kgf.The fringe orders were evaluated around the screws. In all the models analyzed the shear stress were calculated. Results: Independently of the applied load, the smaller screw showed higher values of shear stress.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…And consequently, the higher the stress in the most important area near the screw head, as shown in Fig. 5B(b) 35 . This distribution also occurred in a prosthetic screw after preload 36 .…”
Section: Discussionmentioning
confidence: 97%
“…And consequently, the higher the stress in the most important area near the screw head, as shown in Fig. 5B(b) 35 . This distribution also occurred in a prosthetic screw after preload 36 .…”
Section: Discussionmentioning
confidence: 97%
“…The results showed that the screw-vertebra interface stresses in the IFC model were obviously lower than those of the ACPC models in flexion-extension and lateral bending, and higher during rotation. It can thus be concluded that IFC can effectively reduce the risk of screw loosening in most motion conditions [28], and as such, IFC may provide an option to reduce screw-related complications.…”
Section: Discussionmentioning
confidence: 99%
“…the polyurethane screws. This is due to the presence of localised stresses in a relatively small area of fixation [30]. In terms of average stresses, it can be inferred from table 4 in the standalone femur; it is less than the conventional model; however, the stress is even lower in the proposed design.…”
Section: Total or Equivalent Stressesmentioning
confidence: 86%
“…The values of maximum strain in natural bone and the proposed prosthesis are comparable. However, maximum strain in the conventional design is high, which is expected because of the localized stresses discussed above [30]. Maximum straining occurs at the femoral shaft for each design.…”
Section: Equivalent Strainmentioning
confidence: 94%